2010
DOI: 10.17660/actahortic.2010.882.74
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Date Palm (Phoenix Dactylifera) Pits Extracts and Its Role in Reducing the Side Effect of Methyl Prednisolone on Some Neurotransmitter Content in the Brain, Hormone Testosterone in Adulthood

Abstract: The present work was carried out to study the impact of date palm pits as antibacterial activities on two species of pathogenic bacteria (klebsiella pneumonia and Escherichia coli) and its role in reducing side effect of methylprednisolone on the some neurotransmitter content in the brain, hormone testosterone and testclture of male albino rats .Date palm pits is most effective in inhibiting growth of bacteria as compared with antibiotics due to differences in resistance of bacteria to anti-tested materials du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
2
22
1
1
Order By: Relevance
“…Water and alcoholic extracts of date-pits showed anti-microbial activity against Klebsiella pneumonia, Escherichia coli [Mossa et al, 1986], Staphylocaccus aurus, Proteus vulgaris, and Bacillus subtilis [Saddiq & Bawazir, 2010]. Date-pits are most effective in inhibiting the growth of bacteria as compared to antibiotics, mainly due to two reasons: i) differences in resistance of bacteria to anti-tested materials, and ii) the change in membrane permeability of cells, thereby hindering the entry of enzymes or excreted by the change in the chemical composition of the constituent chemical [Mossa et al, 1986;Saddiq & Bawazir, 2010].…”
Section: Date-pits As An Antimicrobial Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Water and alcoholic extracts of date-pits showed anti-microbial activity against Klebsiella pneumonia, Escherichia coli [Mossa et al, 1986], Staphylocaccus aurus, Proteus vulgaris, and Bacillus subtilis [Saddiq & Bawazir, 2010]. Date-pits are most effective in inhibiting the growth of bacteria as compared to antibiotics, mainly due to two reasons: i) differences in resistance of bacteria to anti-tested materials, and ii) the change in membrane permeability of cells, thereby hindering the entry of enzymes or excreted by the change in the chemical composition of the constituent chemical [Mossa et al, 1986;Saddiq & Bawazir, 2010].…”
Section: Date-pits As An Antimicrobial Agentmentioning
confidence: 99%
“…Date-pits are most effective in inhibiting the growth of bacteria as compared to antibiotics, mainly due to two reasons: i) differences in resistance of bacteria to anti-tested materials, and ii) the change in membrane permeability of cells, thereby hindering the entry of enzymes or excreted by the change in the chemical composition of the constituent chemical [Mossa et al, 1986;Saddiq & Bawazir, 2010].…”
Section: Date-pits As An Antimicrobial Agentmentioning
confidence: 99%
“…Its extract was found to exhibit strong antimicrobial activity against various types of microorganisms such as, bacteria (Saddiq and Bawazir, 2010), fungi (Shraideh et al, 1998) and viruses (Jassim and Naji, 2010). Also, date palm extract was found to have a strong hepatoprotective activity against various harmful toxicants (Saafi et al, 2011;Al-Qarawi et al, 2005) from results obtained from histological and biochemical measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of activity may also be due to the solvent used and the type of bacteria. Saddiq and Bawazir (2010), for example, found that Klebsiella pneumonia and Escherichia coli growth was inhibited by treatment with P. dactylifera water extracts, with inhibition zones of 16.351 and 10.00 mm, respectively. Further, an acetone extract of P. dactylifera was shown to be a potential antiviral agent against pathogenic human viruses (Jassim and Naji, 2007).…”
Section: Ajptmentioning
confidence: 99%